TERRESTRIAL TARDIGRADES AROUND SYOWA STATION (ABSTRACT) (16th Symposium on Polar Biology) - ウツギ, カズオ; オオヤマ, ヨシクニ; UTSUGI, Kazuo; OHYAMA, Yoshikuni (National Institute of Polar Research, 1995)
P(論文) departmental bulletin paper